2015
DOI: 10.18632/oncotarget.5430
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma cells can corrupt senescent mesenchymal stromal cells and impair their anti-tumor activity

Abstract: Senescent cells secrete several molecules that help to prevent the progression of cancer. However, cancer cells can also misuse these secreted elements to survive and grow. Since the molecular and functional bases of these different elements remain poorly understood, we analyzed the effect of senescent mesenchymal stromal cell (MSC) secretome on the biology of ARH-77 myeloma cells. In addition to differentiating in mesodermal derivatives, MSCs have sustained interest among researchers by supporting hematopoies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The SASP secretome consist of growth factors and cytokines including interleukin-1 (IL-1), IL-3, IL-4, IL-6, IL-8, epidermal growth factor), hepatocyte growth factor, insulin growth factor, platelet derived growth factor, TGF-and vascular endothelial growth factor (VEGF) [46] that amongst their other roles, regulate MSCs proliferation in culture and are crucial to MSC senescence as well [2]. Senescent MSC secretome can induce senescence and apoptosis in other cells [47], as well an inflammatory responses in neighbouring cells [16,27]. Critically, transplantation of even small numbers of senescent cells can cause age-related disease phenotypes, such as osteoarthritis, as shown recently by Xu et al [48].…”
Section: Replicative and Stress-induced Senescence In Msc Cultures: Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The SASP secretome consist of growth factors and cytokines including interleukin-1 (IL-1), IL-3, IL-4, IL-6, IL-8, epidermal growth factor), hepatocyte growth factor, insulin growth factor, platelet derived growth factor, TGF-and vascular endothelial growth factor (VEGF) [46] that amongst their other roles, regulate MSCs proliferation in culture and are crucial to MSC senescence as well [2]. Senescent MSC secretome can induce senescence and apoptosis in other cells [47], as well an inflammatory responses in neighbouring cells [16,27]. Critically, transplantation of even small numbers of senescent cells can cause age-related disease phenotypes, such as osteoarthritis, as shown recently by Xu et al [48].…”
Section: Replicative and Stress-induced Senescence In Msc Cultures: Mmentioning
confidence: 99%
“…Senescent cell accumulation is likely to be responsible for a decrease in the overall multipotent differentiation ability of long term expanded MSCs [26,49]. Finally, senescent cells SASP can accelerate ageing [48] or induce apoptosis [47] in the neighbouring cells. Thus, having a direct method for identification, quantification and ultimately, removal of senescent cells in MSC cultures would have a significant value for ensuring the quality of MSCs intended for clinical applications.…”
Section: Replicative and Stress-induced Senescence In Msc Cultures: Mmentioning
confidence: 99%
“…Although many studies highlighted the importance of the SASP in regulating cellular response to senescence signaling, the identification of secreted factors is still a challenging issue, since the typology of secreted proteins strictly depends on genotoxic stress and cell type (2)(3)(4). To date, a comprehensive analysis of the secretome profile of senescent MSCs is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is the permanent cell cycle arrest evoked in response to a variety of stressors (1). This physiological response to stress has a pleiotropic effect: i) beneficial, since senescence can counteract tumor growth by blocking the proliferation of transformed cells, ii) detrimental by contributing to organismal aging (2)(3)(4). Recently, it has been demonstrated that senescence may also contribute to organism development and tissue repair processes (5).…”
Section: Introductionmentioning
confidence: 99%
“…These different results could be due to the effect of cancer cells on MSCs. Actually, the SASP of naïve senescent cells (not primed by cancer cells) may block the proliferation and induce senescence of an immortalized lymphoblastoid cell line, whereas primed senescent MSCs show an impaired anti-proliferative and pro-senescence activity due to a significant modification of the SASP composition induced by priming with cancer cells [179]. Moreover, treatment of immortalized prostate and metastatic prostatic cancer cell lines with the SASP from naïve acute senescent MSCs induced senescence of immortalized cells but not of cancer cells [180].…”
Section: Sasp: In Vitro Datamentioning
confidence: 99%